The Opinion Of Students Toward The Importance Of English Language Learning As An Obligatory Subject In The Social Welfare Science Class At Stisipol Candradimuka Palembang - Sherly Desliyanah (Pusat Riset dan Inovasi Nasional, 2023)
This study was conducted to know the opinion of students towards the importance of English language learning as an obligatory subject in the social welfare science class at Stisipol Candradimuka Palembang. The qualitative survey research method was applied with 50 respondents who came from Social welfare science class in Stisipol Candradimuka Palembang. The research study result showed 84% of the respondents stated that learning English helps them to get more opportunities to get a better job after graduation. Meanwhile, 94% of the respondents stated that ‘listening, speaking, reading, writing’ are all important in learning English. The study result showed that English language learning as a compulsory subject in the class of social welfare science is important.